On the Norm of Decomposable Subgroups in Locally Finite Groups - Lyman, F. N.; Lukashova, T. D. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study the relationships between the norm of decomposable subgroups and the norm of Abelian noncyclic subgroups in the class of locally finite groups. We also describe some properties of periodic locally nilpotent groups in which the norm of decomposable subgroups is a non-Dedekind norm.